Effect of various coumarins on the intestinal absorption of galactose in vivo (Revista Española de Fisiología, 1975)
The effect of various coumarins on the active transport of galactose by small intestine in chick and rat was studied, using the in vivo technique of sucessive absorptions. A 10(-4) M concentration of the different coumarins inhibits the absorption of galactose in the chick. This effect persists in successive absorptions without coumarin. In rat, inhibition of galactose active transport by coumarins was observed at 10(-3) M concentration.